2021
DOI: 10.1001/jamanetworkopen.2021.34627
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dimethyl Fumarate vs Fingolimod and Rituximab vs Natalizumab for Treatment of Multiple Sclerosis

Abstract: Key Points Question In the management of multiple sclerosis, is there a difference in relapse outcomes associated with commonly prescribed, standard-efficacy medications as well as with common higher-efficacy medications? Findings This comparative effectiveness study integrated electronic health records with research registry data and found no significant differences in relapse outcomes between dimethyl fumarate and fingolimod after correcting for confoundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…3,4 The available MS disease-modifying therapies (DMTs) pose soaring costs and exhibit variable real-world effectiveness in preventing inflammatory disease activity and delaying disability worsening. [5][6][7] In the current practice, clinicians primarily rely on history, exams and neuroimaging to assess MS disease activity, disability progression, and treatment response. There is an unmet need to improve disease monitoring at the point of care to guide individualized management.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The available MS disease-modifying therapies (DMTs) pose soaring costs and exhibit variable real-world effectiveness in preventing inflammatory disease activity and delaying disability worsening. [5][6][7] In the current practice, clinicians primarily rely on history, exams and neuroimaging to assess MS disease activity, disability progression, and treatment response. There is an unmet need to improve disease monitoring at the point of care to guide individualized management.…”
Section: Introductionmentioning
confidence: 99%
“…Based on their statistical algorithms, there was an increased 1-year (0.08 rate difference), 2-year (0.132 rate difference) and shorter time to related (0.903 rate difference) in natalizumab-treated patients compared to rituximab. Interestingly, there were no significant difference in relapses between dimethyl fumarate and fingolimod in all three outcome measures (150).…”
Section: Injectable Vs Oral Dmts Vs High-efficacy Dmtmentioning
confidence: 81%
“…In this study, the oral DMT group demonstrated a lower time to first relapse (HR 0.57, 95% CI 0.47, 0.69) and annualized relapse rate (0.65 incidence ratio, 95% CI 0.52, 0.82) but no difference in the disability progression between the injectable and oral DMT groups (149). A comparative effectiveness study used an MS research registry and the electronic health record of 1,535 patients in the registry to determine 1-year, 2-year relapse rate and time to relapse for patients treated with dimethyl fumarate, fingolimod, natalizumab and rituximab after adjusting for confounders and propensity scores (150). The study compared natalizumab with rituximab, and dimethyl fumarate with fingolimod.…”
Section: Injectable Vs Oral Dmts Vs High-efficacy Dmtmentioning
confidence: 99%
“…In our analysis, we adjusted for key covariates (age, sex, race, region, time since MS cohort entry, and ECI) readily available from the claims data. Our recent study highlighted the value of incorporating electronic health record (EHR) data as high-dimensional covariates in real-world comparative analysis of MS [ 32 ]. In future studies, we will perform integrated analysis of claims and EHR data to compare long-term healthcare utilization, expenditure, and disability (based on computed phenotype from claims and/or EHR data) across the treatment groups after better accounting for confounders.…”
Section: Discussionmentioning
confidence: 99%